Vagueness, inconsistency, and semantic competence - Davies, W (2008)
I defend Cognitive Inconsistentism, a novel explanation of vagueness qua susceptibility to sorites paradoxes. The view is contrasted with the Inconsistency Theories of Michael Dummett and Matti Eklund. I argue that these latter views are committed to unattractive theories of linguistic understanding. I propose an alternative Chomskyan, cognitive theory of linguistic understanding. I employ this cognitive framework to argue that speakers mentally represent a similarity constraint on conceptual classification, which is causally and explanatorily implicated in language acquisition and use. This cognitive similarity constraint causally explains our linguistic intuitions with respect to sorites paradoxes.